Highly diverse microbial community of regenerated seedlings reveals the high capacity of the bulb in lily, Lilium brownii - Jibril, Sauban Musa; Yan, Wu; Wang, Yi; Zhu, Xishen; Yunying, Zhou; Wu, Jie; Wang, Ling; Zhang, Limin; Li, Chengyun (Frontiers in Microbiology, 2024)
Lily bulbs, which have both nutrient storage and reproductive functions, are a representative group of plants for studying the maintenance and transfer of plant-associated microbiomes. In this study, a comparison of the microbial composition of bulbs and their regenerated seedlings cultured under aseptic conditions, as well as subcultured seedlings that succeeded five times, was examined by amplicon sequencing. A total of 62 bacterial taxa and 56 fungal taxa were found to be transferred to the 5th generation in seedlings, which are the core microbiome of lily. After the regeneration of seedlings from bulbs, there was a significant increase in the number of detectable microbial species, and after 1, 3, and 5 successive generations, there was a decrease in the number of detectable species. Interestingly, some "new" microorganisms appeared in each generation of samples, for instance, 167 and 168 bacterial operational taxonomic units (OTUs) in the 3rd and 5th generations of seedlings that were not detected in either bulbs or seedlings of the previous two generations. These results suggest that bulbs can maintain a high diversity of microorganisms, including some with ultra-low abundance, and have a high transfer capacity to tuck shoots through continuous subculture. The diversity and maintenance of the microbiome can provide the necessary microbial reservoir support for regenerating seedlings. This habit of maintaining low abundance and high diversity may be biologically and ecologically critical for maintaining microbiome stability and function due to the sequestration nature of the plant.